2021
DOI: 10.1021/acssensors.0c01933
|View full text |Cite
|
Sign up to set email alerts
|

Missing-Linker 2D Conductive Metal Organic Frameworks for Rapid Gas Detection

Abstract: The structural diversity and tunability of metal organic frameworks (MOFs) represent an ideal material platform for a variety of practical scenarios ranging from gas storage/separation to catalysis, yet their application in chemiresistive gas sensing is relatively lacking, due to the requirements of combined electrical conductivity and optimized gas adsorption properties. Here, we report an effective chemical sensing strategy based on missing-linker two-dimensional conductive MOF, with incorporated defects via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 80 publications
(113 reference statements)
0
21
0
Order By: Relevance
“…Tailor-made molecular design is also attractive for the rational design of MOFs-based gas sensors. Mirica et al utilized a heterobimetallic 2D conducting MOFs with metallophthalocyanine units interconnected via Cu nodes to achieve ultrahighly sensitive detection of ppm levels of carbon monoxide (CO) at RT. Figure k shows the SEM image of the CoPc-O 8 -Cu MOF.…”
Section: Gas-sensitive Effect Of Low-dimensional Semiconductor Nanoma...mentioning
confidence: 99%
“…Tailor-made molecular design is also attractive for the rational design of MOFs-based gas sensors. Mirica et al utilized a heterobimetallic 2D conducting MOFs with metallophthalocyanine units interconnected via Cu nodes to achieve ultrahighly sensitive detection of ppm levels of carbon monoxide (CO) at RT. Figure k shows the SEM image of the CoPc-O 8 -Cu MOF.…”
Section: Gas-sensitive Effect Of Low-dimensional Semiconductor Nanoma...mentioning
confidence: 99%
“…Despite these promising results which reveal the potential of 2D MOFs in tuning and optimising chemiresistive responses, the synthesis of conductive 2D MOFs remains synthetically challenging and limited to conjugated benzene rings and porphyrin rings. 56 To circumvent the low conductivity of MOFs, composite materials have also been synthesised. 25,57 25 The sensor device includes a dried paste containing carbon black or single walled carbon nanotubes and polytetrafluoroethylene (PTFE) which are placed as a film on glass slides using silver conductive paint.…”
Section: Chemiresistive and Chemicapacitivebased Sensingmentioning
confidence: 99%
“…[34][35][36][37][38] The catalysts could be provided with more active sites, which would improve the electrical conductivity. [39][40][41][42][43] Apart from the fact that Fe and Co have been widely investigated as transition metal electrochemical catalysts, it was found that Cu-embedded catalysts possess higher catalysis performance with higher conductivity and enhanced charge transfer and hence can be considered as a promising candidate. [44][45][46][47] In addition, owing to the high surface area provided by the porous nanocarbon structure, Cu and N codoped carbon (Cu-N/C) catalysts are sought after due to their satisfactory catalysis performance.…”
Section: Introductionmentioning
confidence: 99%